2020
DOI: 10.1002/gcc.22842
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic and atypical KMT2A‐USP2 and KMT2A‐USP8 rearrangements identified by mate pair sequencing in infant and childhood leukemia

Abstract: Infant leukemias are a rare group of neoplasms that are clinically and biologically distinct from their pediatric and adult counterparts. Unlike leukemia in older children where survival rates are generally favorable, infants with leukemia have a 5-year eventfree survival rate of <50%. The majority of infant leukemias are characterized by KMT2A (MLL) rearrangements (~70 to 80% in acute lymphoblastic leukemia), which appear to be drivers of early leukemogenesis. In this report, we describe three cases: a 9-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Gene fusion detection in a diagnostic setting poses several challenges: (1) specific gene fusions may be rare, [7][8][9] (2) breakpoints may be atypical, [10][11][12][13] and (3) fusion partners may be promiscuous. 14 Both reverse transcriptase polymerase chain reaction (RT-PCR)based assays and fluorescence in situ hybridization (FISH) assays using break-apart probes are a sensitive, but time-consuming method to detect chromosomal rearrangements.…”
Section: Introductionmentioning
confidence: 99%
“…Gene fusion detection in a diagnostic setting poses several challenges: (1) specific gene fusions may be rare, [7][8][9] (2) breakpoints may be atypical, [10][11][12][13] and (3) fusion partners may be promiscuous. 14 Both reverse transcriptase polymerase chain reaction (RT-PCR)based assays and fluorescence in situ hybridization (FISH) assays using break-apart probes are a sensitive, but time-consuming method to detect chromosomal rearrangements.…”
Section: Introductionmentioning
confidence: 99%
“…The Mitelman database of chromosome aberrations and gene fusions in cancer has documented 14 chimeric genes involving USP8, including a fusion between USP8 and lysine methyltransferase 2A (KMT2A) in B-cell lineage acute lymphoplastic leukemia. The KMT2A::USP8 chimera was generated by chromosomal translocation t(11;15)(q23;q21) (51,52). The genomic breakpoints occurred within introns 20 and 12 of KMT2A and USP8 (NM_005154), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The translocation of the KMT2A gene produces a KMT2A fusion protein that directly binds to DNA and upregulates gene transcription, leading to the development of acute myeloid leukemia (AML) in infants and children ( 164 , 165 ). USP2 serves as a chaperone gene for KMT2A and the poor clinical prognosis of children with KMT2A - USP2 -positive AML has been associated with the aberrant expression of USP2 ( 166 168 ). In a prospective study, Meyer et al ( 169 ) reported that a very small number of patients with acute leukemia have rearranged USP2 and USP8 genes and that the conserved region of the deubiquitinating enzyme ‘UCH-domain’ fuses to an extended 5´-MLL portion, which formed the fusion proteins MLL-USP2 and MLL-USP8.…”
Section: Targeting Usp2 For Cancer Therapymentioning
confidence: 99%